Redescription of Lernaeenicus longiventris Wilson, 1917 (Copepoda: Pennellidae) parasitic on the Pacific Crevalle Jack Caranx caninus (Carangidae) through morphological and molecular analyses - Juan Manuel Osuna‑Cabanillas; Francisco Neptalí Morales‑Serna; Balu Alagar Venmathi Maran; José Antonio Cruz‑Barraza (Springer Nature, 2023)
Purpose The present study deals with a redescription of the copepod Lernaeenicus longiventris Wilson, 1917 (Copepoda: Siphonostomatoida: Pennellidae) found on the Pacifc crevalle jack Caranx caninus Günther, using morphological and molecular analyses. Methods Fish were collected of Mazatlán Port (23° 12′ N, 106° 26′ W), in the State of Sinaloa, Mexico (southeastern Gulf of California). The copepods were morphologically analyzed by light microscopy. Sequences of the COI mtDNA gene were generated for the frst time for this species. These sequences were compared to COI sequences from six species of Lernaeenicus available in GenBank. Results The specimens of the present study exhibited a cephalosome without apparent lateral processes, which were origi‑ nally described for L. longiventris. No remarkable diferences were observed with previous descriptions regarding appendages and body proportions. The phylogenetic tree based on COI sequences showed that L. longiventris was closer to L. radiatus although with low bootstrap values support in ML tree, both species formed a sister clade of L. sprattae. Conclusions Lernaeenicus longiventris is the unique species of the genus in the Mexican Pacifc and the Gulf of California, and also the unique species of Lernaeenicus infecting C. caninus. Molecular data of L. longiventris from host and locality type are required to avoid misidentifcation of this species.